1965
DOI: 10.1113/expphysiol.1965.sp001792
|View full text |Cite
|
Sign up to set email alerts
|

The Golgi Apparatus in Small Lymphocytes and in Transformed Blast Cells

Abstract: Chalmers, 1964] were diluted with warmed TC 199 culture medium (Glaxo) in sterile siliconed universals with white rubber liners, and then cultured. These cultures were made from the blood of the same healthy donors who provided the fresh small lymphocytes. These donors, A.C., D.W., and L.F. had previously had prophylactic tetanus toxoid injections. The tissue culture cell concentration was adjusted to 1000 small lymphocytes/cu.mm. Adsorbed tetanus toxoid, Tet/Vac/ADS (Burroughs Wellcome), was used as the antig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1966
1966
1977
1977

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The initial investigation of NDPasc activity was made because it was considered that this enzyme was associated with the Golgi apparatus and that a high NDPase activity might be an indication that a cell was able to secrete protein (Sjostrand and Hansen, 1954;Porter, 1961;Coulson, 1965). The present studies showed that there was a considerable variation in the activity of the enzyme which was not related to any particular stage of the cell cycle.…”
Section: Discussionmentioning
confidence: 73%
“…The initial investigation of NDPasc activity was made because it was considered that this enzyme was associated with the Golgi apparatus and that a high NDPase activity might be an indication that a cell was able to secrete protein (Sjostrand and Hansen, 1954;Porter, 1961;Coulson, 1965). The present studies showed that there was a considerable variation in the activity of the enzyme which was not related to any particular stage of the cell cycle.…”
Section: Discussionmentioning
confidence: 73%
“…Incubation for 60 min produced denser staining than 30 min. [Coulson, 1970], and nucleoside diphosphatase on the Golgi membranes [Coulson, 1965] of the transformed cell, the latter structure possibly being active in the secretion of lymphokines. A subsequent study [Coulson and Kennedy, 1971] showed that cyclic AMPase was localized on the nuclear membrane, although a definite role has not yet been established for this enzyme in the stimulation pathway.…”
Section: Localization Of the Atpasementioning
confidence: 99%